Interaction of Human Tumor Cells with Human Platelets and the Coagulation System - Al-Mondhiry, Hamid; McGarvey, Virginia; Leitzel, Kim (Thrombosis and Haemostasis, 1983)
This paper reports studies on the interaction between human platelets, the plasma coagulation system, and two human tumor cell lines grown in tissue culture: Melanoma and breast adenocarcinoma. The interaction was monitored through the use of 125I- labelled fibrinogen, which measures both thrombin activity generated by cell-plasma interaction and fibrin/fibrinogen binding to platelets and tumor cells. Each tumor cell line activates both the platelets and the coagulation system simultaneously resulting in the generation of thrombin or thrombin-like activity. The melanoma cells activate the coagulation system through “the extrinsic pathway” with a tissue factor-like effect on factor VII, but the breast tumor seems to activate factor X directly. Both tumor cell lines activate platelets to “make available” a platelet- derived procoagulant material necessary for the conversion of prothrombin to thrombin. The tumor-derived procoagulant activity and the platelet aggregating potential of cells do not seem to be inter-related, and they are not specific to malignant cells.
Keywords: Factor VIII; Age; Haemophilia; Carriers